Hydrogen Adsorption Characteristics for Zeolite-Y Templated Carbon - Rika Wijiyanti; Triyanda Gunawan; Noor Shawal Nasri; Zulhairun Abdul Karim; Ahmad Fauzi Ismail; Nurul Widiastuti (Indonesian Journal of Chemistry, 2020)
The hydrogen adsorption, kinetic and thermodynamic of adsorption onto the zeolite templated carbon (ZTC) were examined at the temperature range of 30-50 °C and ambient pressure. The ZTC was prepared from zeolite-Y template and sucrose carbon precursor by impregnation method and showed its specific surface area of 932 m2/g as well as 0.97 cm3/g for total pore volume. Analysis of physical and chemical characteristics for materials were performed using XRD, SEM, TEM and N2 isotherm. The results indicated that the ZTC has some ordered network structure of carbon and also exhibits the formation of carbon layer outside the zeolite micropore. We observed the ZTC for hydrogen adsorption both gravimetric and volumetric method up to 1.72 and 1.16 wt.% at the lowest temperature, respectively. The kinetic process at all studied temperature was best approximated by pseudo second order kinetic model. The aspects of thermodynamic such as heat of adsorption and the entropy change were -14.41 kJ/mol and -40.93 J/K mol, respectively. Both values was negative, indicating an exothermic reaction and low disorder at the hydrogen and ZTC interface, when the adsorption process took place. While, the enthalpy change value exhibits characteristic of physical process. The Gibbs energy change calculated at 30, 40 and 50 °C were -1.99, -1.59 and -1.19 kJ/mol, respectively, indicating a spontaneous adsorption process.